Geometrical visualisation of indirect space vector modulation for matrix converters operating with abnormal supplies. Issue 15 (7th November 2019) - Guan, Quanxue; Wheeler, Pat; Simon, Olaf; Guan, Quansheng; Clare, Jon
Abstract : Matrix converters can be sensitive to abnormal supply conditions due to the absence of energy storage elements. This sensitivity can get worse when the matrix converters are modulated by a traditional indirect space vector modulation that assumes the input variables are sinusoidal and balanced. Therefore, this study proposes a methodology for the modulation of matrix converters without requiring any assumption of the input voltages. The method uses a geometric representation based on the singular value decomposition of the switch states to synthesise the rotating vectors of the target duty‐cycle matrix. Furthermore, this study mathematically highlights the factors that regulate the amplitude of the output voltages and utilise them to compensate the adverse effect of the abnormal input voltages. Experimental results presented in this study validate that the proposed method can provide sinusoidal and balanced output currents in the presence of abnormal supply conditions.